The Parent Psychological Flexibility Questionnaire (PPFQ): Item Reduction and Validation in a Clinical Sample of Swedish Parents of Children with Chronic Pain - Camilla Wiwe Lipsker; Marie Kanstrup; Linda Holmström; Mike Kemani; Rikard K. Wicksell (MDPI AG, 2016)
In pediatric chronic pain, research indicates a positive relation between parental psychological flexibility (i.e., the parent's willingness to experience distress related to the child's pain in the service of valued behavior) and level of functioning in the child. This points to the utility of targeting parental psychological flexibility in pediatric chronic pain. The Parent Psychological Flexibility Questionnaire (PPFQ) is currently the only instrument developed for this purpose, and two previous studies have indicated its reliability and validity. The current study sought to validate the Swedish version of the 17-item PPFQ (PPFQ-17) in a sample of parents (n = 263) of children with chronic pain. Factor structure and internal reliability were evaluated by means of principal component analysis (PCA) and Cronbach's alpha. Concurrent criterion validity was examined by hierarchical multiple regression analyses with parental anxiety and depression as outcomes. The PCA supported a three-factor solution with 10 items explaining 69.5% of the total variance. Cronbach's alpha (0.86) indicated good internal consistency. The 10-item PPFQ (PPFQ-10) further explained a significant amount of variance in anxiety (29%), and depression (35.6%), confirming concurrent validity. In conclusion, results support the reliability and validity of the PPFQ-10, and suggest its usefulness in assessing psychological flexibility in parents of children with chronic pain.